SIMULASI NUMERIK FLOAT PESAWAT 19 PENUMPANG DENGAN STRUKTUR CARBON-EPOXY COMPOSITE KETIKA LANDING DI PERMUKAAN AIR: NUMERIC SIMULATION OF 19 PASSENGER AIRCRAFT FLOAT WITH CARBON-EPOXY COMPOSITE STRUCTURE WHEN LANDING ON THE WATER SURFACE - Dwi Juniarsah, Fahri; Sitompul, Sahril Afandi; Yuniarti, Endah (Jurnal Teknologi Kedirgantaraan, 2023)
The 19-passenger aircraft can be modified into a seaplane by providing it with a floating device in the form of a float. The use of float is very advantageous because it does not change the configuration of the fuselage much, but the mass and design of the float must be adjusted so that the performance of the aircraft does not decrease. Impact between the water and the float structure can create critical loads or even cause structural damage. The purpose of this research is optimizing the direction of the composite fiber by comparing the four arrangement of fiber directions by looking at the results of the Tsai-Hill failure criteria. In addition, the finite element method simulation is carried out in static simulation conditions to determine the response of the float structure with Carbon-epoxy material due to static loading based on variations in pressure loads during landing and to determine the effect of composite thickness on pressure distribution. which is applied to the bottom surface of the float. From the analysis, it was found that the most optimal fiber direction was [0o2/45o2/-45o2/90o2]s with a composite thickness of 2 mm. The biggest displacement is at the back of the float. In the condition of the pressure load when VS0 the received stress is 202.422 MPa. The current received stress VREF 352,927 MPa. When the speed is 70 knots, the received stress is greater, namely 437.876 MPa with a Tsai-Hill value of 0.2622. This indicates that Carbon-epoxy is ideal for use as a float material because of its resistance to high stresses.